2017
DOI: 10.1016/j.amjmed.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Magnesium on Mortality in Patients Admitted to the Intensive Cardiac Care Unit

Abstract: This retrospective study unexpectedly observed no association between serum magnesium levels and QTc interval or sudden cardiac death. However, serum magnesium ≥2.4 mg/dL was an independent predictor of increased hospital morality among CCU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 32 publications
3
48
1
Order By: Relevance
“…50,51) However, no association has been reported between serum magnesium levels and QTc interval. 29) Fourth, we could not analyze our data stratified by sex because of the small sample size. Nevertheless, we assessed the relationship between the ADPN level and clinical characteristics including ECG parameters and the odds ratio for QTc prolongation in ADPN tertiles according to the sex-specific tertiles of ADPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51) However, no association has been reported between serum magnesium levels and QTc interval. 29) Fourth, we could not analyze our data stratified by sex because of the small sample size. Nevertheless, we assessed the relationship between the ADPN level and clinical characteristics including ECG parameters and the odds ratio for QTc prolongation in ADPN tertiles according to the sex-specific tertiles of ADPN.…”
Section: Discussionmentioning
confidence: 99%
“…The QTc intervals were calculated using Bazett's formula (QTc = QT / RR). 28,29) In brief, the ECG tracings were blinded to the participants' demographics and first analyzed by two independent cardiologists and a senior supervising cardiologist. Inter-reader discrepancies were resolved by direct comparison and adjudicated by the supervising cardiologist.…”
Section: Study Populationmentioning
confidence: 99%
“…Pickham et al showed that hyperglycaemia is linked with QTc prolongation. 54 Moreover, whether albumin is associated with the expression of cardiac ion channels, cardiomyocyte electrophysiology, and the underlying mechanism are still unclear. 49 In our study, we also found that the QTc interval was negatively associated with eGFR and albumin level.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies reported that hypomagnesaemia has been associated with atrial and ventricular arrhythmias and low serum magnesium could therefore also be a risk factor for sudden cardiac death, 52,53 no association was found between serum magnesium levels and QTc interval. 54 Moreover, whether albumin is associated with the expression of cardiac ion channels, cardiomyocyte electrophysiology, and the underlying mechanism are still unclear. Further investigations are warranted to elucidate these issues.…”
Section: Despite the Strong Evidence Showing The Effect Of Serum Albumentioning
confidence: 99%
“…Likewise, studies examining associations between plasma zinc and number of organ failures, or associations between low plasma levels of magnesium, phosphate or zinc and mortality have been contradictory . In addition, observational studies examining hypermagnesaemia and hyperphosphataemia have typically reported the inverse association of increased mortality as compared with lower plasma levels …”
Section: Introductionmentioning
confidence: 99%